Datação por radiocarbono-AMS do Sítio Arqueológico Justino, Canindé de São Francisco, Sergipe - Santana, Alquizia Dorcas Dantas de (2013)
This study aimed to obtain the chronologies of the occupation of Justin Cemeteries Archeological Site, located in Canindé San Francisco, State of Sergipe. The ages were obtained by dating isotope 14C using the technique of Accelerator Mass Spectrometry (AMS), Beta Analytic Laboratory (USA). Were initially selected for analysis samples of human teeth and bones, respectively, but these materials showed no collagen volume allowing the dating. Thus, selected samples of charcoal four layers of stratigraphic site, which fires occurred in old structures. The results show four distinct cycles of human occupation in the region Xingó, namely 2510 ± 30 BP, 4390 ± 30 BP, 7530 ± 30 and 12220 ± 50 AP AP. These new radiocarbon dating conducted for Site Justin Caninde show that culture is much older than hitherto had knowledge, kicking the arrival of these populations to the Quaternary period and Pleistocene epoch.